The Impact of External Visual Attention on Working Memory Performance in Multitasking Tasks - Frederick, Alvarez; Desiderio, Desiderio; Laetitia, Grettina (PELNUS | Pen en Light for Natural Union of Science, 2025)
This study investigates the impact of external visual attention on working memory performance during multitasking conditions. The research aims to understand how varying levels of attentional load influence memory accuracy and reaction time, and whether individual differences in attentional control moderate these effects. Using an experimental within-subject design, participants performed a primary working memory task (visual n-back test) alongside a secondary visual attention task involving distractor stimuli. Measures included reaction time, recall accuracy, and eye-tracking data to capture cognitive processing dynamics. The findings reveal that increased external visual attention or distraction significantly reduces working memory accuracy and increases reaction time, indicating heightened cognitive interference under high attentional load. Furthermore, results show that individuals with stronger attentional control experience less impairment in memory performance, suggesting a protective effect of attentional regulation. These outcomes support theoretical models of limited attentional resources, demonstrating that visual distractions compete with working memory processes for cognitive capacity. The study contributes to a deeper understanding of how attention and memory interact under multitasking conditions. Practically, the results have implications for optimizing human-computer interfaces, improving learning environments, and enhancing workplace productivity by minimizing visual distractions. Overall, this research underscores the importance of attentional management in preserving cognitive efficiency and performance accuracy in complex, multitasking settings.